Genome-wide screen of Saccharomyces cerevisiae null allele strains identifies genes involved in selenomethionine resistance - Bockhorn, Jessica (National Academy of Sciences, 2008)
Selenomethionine (SeMet) is a potentially toxic amino acid, and yet it is a valuable tool in the preparation of labeled proteins for multiwavelength anomalous dispersion or single-wavelength anomalous dispersion phasing in X-ray crystallography. The mechanism by which high levels of SeMet exhibits its toxic effects in eukaryotic cells is not fully understood. Attempts to use Saccharomyces cerevisiae for the preparation of fully substituted SeMet proteins for X-ray crystallography have been limited. A screen of the viable S. cerevisiae haploid null allele strain collection for resistance to SeMet was performed. Deletion of the CYS3 gene encoding cystathionine gamma-lyase resulted in the highest resistance to SeMet. In addition, deletion of SSN2 resulted in both increased resistance to SeMet as well as reduced levels of Cys3p. A methionine auxotrophic strain lacking CYS3 was able to grow in media with SeMet as the only source of Met, achieving essentially 100% occupancy in total proteins. The CYS3 deletion strain provides advantages for an easy and cost-effective method to prepare SeMet-substituted protein in yeast and perhaps other eukaryotic systems.